PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN WORDWALL TERHADAP KEMAMPUAN BERFIKIR TINGKAT TINGGI PADA PEMBELAJARAN MATEMATIKA - Nuraini Lutfin Nisa; Rida Fironika Kusumadewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the Problem Based Learning (PBL) model assisted by Wordwall media on students’ higher-order thinking skills and learning outcomes in mathematics, specifically on the topic of perimeter of plane figures. The research was conducted at SD Negeri 3 Brabo involving 20 fifth-grade students, divided into an experimental group and a control group. The study used a true-experimental design with a posttest-only control design. Instruments included higher-order thinking skill tests and mathematics learning outcome tests. Data were analyzed using normality tests, homogeneity tests, and t-tests. The results showed that the experimental group outperformed the control group in both higher-order thinking skills and mathematics learning outcomes. These findings indicate that the implementation of the PBL model with Wordwall media had a significant influence on students' learning performance regarding the perimeter of plane figures.